2017
DOI: 10.18632/oncotarget.17307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circular RNAs as a promising new class of diagnostic biomarkers for human breast cancer

Abstract: Endogenous noncoding circular RNAs (circRNAs) have gained attention for their involvement in carcinogenesis, but their expression pattern in breast cancer has remained largely unknown. In this two-stage study, we first used an Arraystar Human circRNA Array to construct a genome-wide circRNA profile. We then selected candidate circRNAs for validation using a quantitative real-time polymerase chain reaction system. CircRNA/miRNA interactions were predicted and sequence analyses were performed. Among 1155 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 58 publications
1
108
0
Order By: Relevance
“…In the recent years, circRNAs have received considerable attention because accumulating evidences indicate that they play important roles in the development and progression of various cancers through functioning as a sponge for miRNAs (Kristensen, Hansen, Venø, & Kjems, 2018;Kulcheski, Christoff, & Margis, 2016;Wang, Xiao, Wu, & Ma, 2018). In the case of BC, several recent reports have demonstrated the key roles of dysregulated circRNAs in the breast tumor development as well as its clinicopathological outputs, thereby show diagnostic and therapeutic biomarker values (Lü et al, 2017; H. Wang, Xiao, et al, 2018).…”
Section: Circrnasmentioning
confidence: 99%
“…In the recent years, circRNAs have received considerable attention because accumulating evidences indicate that they play important roles in the development and progression of various cancers through functioning as a sponge for miRNAs (Kristensen, Hansen, Venø, & Kjems, 2018;Kulcheski, Christoff, & Margis, 2016;Wang, Xiao, Wu, & Ma, 2018). In the case of BC, several recent reports have demonstrated the key roles of dysregulated circRNAs in the breast tumor development as well as its clinicopathological outputs, thereby show diagnostic and therapeutic biomarker values (Lü et al, 2017; H. Wang, Xiao, et al, 2018).…”
Section: Circrnasmentioning
confidence: 99%
“…In parallel with functioning as transcription and translation regulator, the ecRNAs act as miRNAs sponges enjoying MREs [9]. The circRNA profile of BC versus normal tissues introduces manifold anti-breast cancer controllable targets [10]. Suppression of circIRAK3 leads to down-regulation of FOXC1 through miR-3607-FOXC1 axes and promotes BC cell metastasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Lu et al, among 1,155 differentially expressed circRNAs, a total of 715 circRNAs were notably overexpressed, and 440 were remarkably downregulated in the BC lesions compared with healthy tissue samples. Investigators also demonstrated that hsa_circ_103110, hsa_circ_104689, and hsa_circ_104821 levels were surprisingly elevated in BC tissue samples in contrast with healthy ones; whereas hsa_circ_406697, hsa_circ_100219, and hsa_circ_006054 were significantly downregulated(Lu et al, 2017).…”
mentioning
confidence: 99%